2013
DOI: 10.1083/jcb.201302049
|View full text |Cite
|
Sign up to set email alerts
|

Injury-induced BMP signaling negatively regulates Drosophila midgut homeostasis

Abstract: Injury-induced BMP signaling in the midgut negatively regulates intestinal stem cell division, whereas regional constitutive BMP signaling promotes copper cell differentiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
198
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(214 citation statements)
references
References 67 publications
15
198
0
1
Order By: Relevance
“…Many conserved signal transduction pathways regulate ISC behavior following injury, including the EGF, JAK/STAT, Wingless/Wnt, TGF-β/Dpp and insulin pathways (Biteau and Jasper, 2011;Choi et al, 2011;Cordero et al, 2012;Guo et al, 2013;Jiang et al, , 2009Lee et al, 2009;Li et al, 2013b;O'Brien et al, 2011;Tian and Jiang, 2014;Xu et al, 2011). The interplay between these different signaling pathways ensures homeostatic renewal as well as rapid regenerative responses to injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many conserved signal transduction pathways regulate ISC behavior following injury, including the EGF, JAK/STAT, Wingless/Wnt, TGF-β/Dpp and insulin pathways (Biteau and Jasper, 2011;Choi et al, 2011;Cordero et al, 2012;Guo et al, 2013;Jiang et al, , 2009Lee et al, 2009;Li et al, 2013b;O'Brien et al, 2011;Tian and Jiang, 2014;Xu et al, 2011). The interplay between these different signaling pathways ensures homeostatic renewal as well as rapid regenerative responses to injury.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies had revealed that several signal transduction pathways are important to control ISC proliferation, in particular the JAK/STAT, epidermal growth factor (EGF) and Decapentaplegic (Dpp)/TGF-β pathways (Biteau and Jasper, 2011;Guo et et al, 2011). We therefore examined whether knockdown of Tnks in ECs resulted in increased expression of the ligands from these pathways using RT-qPCR.…”
Section: Non-autonomous Control Of Jak/stat Signaling In Iscs By Wingmentioning
confidence: 99%
“…Recent studies have revealed an important role for Decapentaplegic (Dpp) signaling in the differentiation of CCs in adult Drosophila [22,23]. GSSCs that are mutant for Dpp signaling components, such as the receptor Thickvein (Tkv) or the downstream transcriptional factor Mothers against Dpp (Mad), can no longer effectively produce CCs [22,23].…”
Section: Notch Activation Is Sufficient To Induce Cc/is Cell Differenmentioning
confidence: 99%
“…GSSCs that are mutant for Dpp signaling components, such as the receptor Thickvein (Tkv) or the downstream transcriptional factor Mothers against Dpp (Mad), can no longer effectively produce CCs [22,23]. To understand the epistatic relationships between Notch and Dpp signaling in CC differentiation, we asked whether forced expression of N icd could induce differentiation of tkv or mad mutant progenitor cells.…”
Section: Notch Activation Is Sufficient To Induce Cc/is Cell Differenmentioning
confidence: 99%
“…Finally, activation of DPP/BMP signalling is required for the return to homeostasis after repair of the damage epithelium has been achieved (Zhou et al, 2014) (Guo et al, 2013).…”
Section: Intestinal Stem Cell Homeostasis During Tissue Regenerationmentioning
confidence: 99%